2006
DOI: 10.3354/meps328093
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of sponge communities in controlling phytoplankton blooms in Florida Bay

Abstract: An unprecedented series of ecological disturbances have been recurring within Florida Bay since the summer of 1987. Persistent and widespread phytoplankton and cyanobacteria blooms have coincided with the large scale decimation of sponge communities. One hypothesis is that the large scale loss of suspension-feeding sponges has rendered the Florida Bay ecosystem susceptible to these recurring blooms. The primary objective of this study was to experimentally evaluate the potential for suspension-feeding sponges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 21 publications
5
127
1
Order By: Relevance
“…Sponges are also important in nitrogen cycling and release large amounts of dissolved inorganic nitrogen that may influence levels of primary production on coral reefs (Southwell et al 2008, Fiore et al 2013. Mass mortality of the Florida Bay sponge community resulted in an increase in the average water column turnover rate by as much as 12 d for some regions of the Bay and could account for the increased algal blooms reported there (Peterson et al 2006). More recently, sponges have been described as essential to the cycling of carbon on coral reefs via the 'sponge loop', whereby sponges consume dissolved organic matter and make carbon available to other reef fauna in the form of detritus (de Goeij et al 2013).…”
Section: Photo: Steven Mcmurraymentioning
confidence: 99%
“…Sponges are also important in nitrogen cycling and release large amounts of dissolved inorganic nitrogen that may influence levels of primary production on coral reefs (Southwell et al 2008, Fiore et al 2013. Mass mortality of the Florida Bay sponge community resulted in an increase in the average water column turnover rate by as much as 12 d for some regions of the Bay and could account for the increased algal blooms reported there (Peterson et al 2006). More recently, sponges have been described as essential to the cycling of carbon on coral reefs via the 'sponge loop', whereby sponges consume dissolved organic matter and make carbon available to other reef fauna in the form of detritus (de Goeij et al 2013).…”
Section: Photo: Steven Mcmurraymentioning
confidence: 99%
“…Cyano bacterial blooms in Florida Bay, perhaps combined with other environmental factors, seem to have disrupted pelagic (Goleski et al 2010) and possibly benthic (Peterson et al 2006) grazing in Florida Bay. Peterson et al (2006) found that sponge mortality in the north-central region of Florida Bay increased water column turnover time by sponge filtration from 3 d to 15 d, and this region of Florida Bay has experienced the most dense and persistent cyanobacterial blooms (Phlips et al 1999, Goleski et al 2010. To date, no study has considered how in situ changes in cyanobacteria blooms affect sponge populations in Florida Bay.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The root cause of these disturbances may be linked to human alterations of the freshwater flow in the Everglades, which is upstream of Florida Bay (Phlips et al 1999, Nuttle et al 2000. These ecological disruptions have resulted in widespread loss of benthic habitat for juvenile fish and spiny lobster (Robblee et al 1991, Butler et al 1995) and a loss of benthic filtration from suspensionfeeding sponges (Peterson et al 2006). These changes could initiate a 'regime shift' from a benthicdominated system to a pelagic-dominated system in some regions of Florida Bay (Chasar et al 2005), which is remarkable considering this system has an average depth of only 1 m (Nuttle et al 2000).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 2 more Smart Citations